Sphingosine 1-phosphate receptor 1 agonists: a patent review (2013-2015). (2nd April 2016) - Guerrero, Miguel; Urbano, Mariangela; Roberts, Edward
ABSTRACT: Introduction: The sphingosine-1-phosphate (S1P) regulates diverse biological functions including cell proliferation, endothelial cell chemotaxis, angiogenesis, immune cell trafficking, mitogenesis, heart rate. The first-in-class S1P1, 3–5 -R pan-agonist fingolimod (FTY720) was approved by the FDA and EMEA for the treatment of relapsing-remitting multiple sclerosis, though the most common adverse effect is bradycardia which occurs in the early stage of treatment and resolves within the first 24 h despite continuing treatment. The underlying mechanism of the cardiovascular effects is the activation of G-protein-gated inwardly rectifying potassium (GIRK) channel by the S1P1 -R. Several second generation S1P1 -R agonists with distinct selectivity, pharmacokinetics and safety profile from FTY720 are under development for the treatment of autoimmune and chronic inflammatory diseases. Areas covered: This review provides a summary of the patent literature from 2013 up to November 2015 on the S1P1 -R agonist molecules and their relevant biological/pharmacological properties. Expert opinion: The molecules reviewed are S1P1 -R agonists with a promising clinical outlook in particular in inflammation and autoimmune diseases. Clinical and preclinical studies of second generation S1P1 -R agonists have been generating interesting results and may finally provide pharmacological agents with improved therapeutic profile than FTY720, particularly in terms of cardiovascular and pulmonary liabilities.